The Methodological Convergences between Symbolic Interactionism and Constructivist Grounded Theory - Salvini, Andrea (Przegląd Socjologii Jakościowej, 2019)
This article explores the connection between Constructivist Grounded Theory (CGT) and Symbolic Interactionism (SI) in the light of the methodological position presented in Herbert Blumer’s Symbolic Interactionism: Perspective and Method. The examination of this connection will take place in three steps: firstly, I will offer some preliminary considerations with regard to ‘variant forms’ in Grounded Theory (GT) as well as cite the present debates about the differences and similarities between different approaches within it; then, I will describe the essential characteristics of the ‘methodological position’ of SI and build some lines of continuity between these elements and the main tenets of constructionist GT; finally, I will present ten conceptual expressions and methodological practices in which it is possible to verify the methodological convergence between the two perspectives. This analysis makes it possible to consider the Constructivist Grounded Theory as a set of coherent principles, methods, and research practices from the point of view of a scholar inspired by the SI’s perspective. However, the peculiar reference to the methodological position of SI does not exhaust the set of possible epistemological and methodological sources, from which the perspective of GT derives. Instead, it represents a controversial point, with regard to which the debate still appears to be particularly heated.